Bangladesh's development agenda and vision 2020 : rhetoric or reality? - Hossain, Moazzem, 1950-; Nurun Nabi, A. K. M.; Islam, Iyanatul, 1953- (Dhaka : University Press, 2003)
Contributed conference papers on economic policies of Sheikh Hasina's tenure in Bangladesh from 1996-2001.
Includes bibliographical references and index.
Keywords: Bangladesh -- Economic policy -- Congresses; Bangladesh -- Social conditions -- Congresses; Bangladesh -- Politics and government -- 1971- -- Congresses